Clays and Clay Minerals, Vol. 57, No. 4, 425–432, 2009. - Kovanda, Frantisek; Masatova, Petra; Novotna, Petra; Jiratova, Kveta (My University, 2009)
Layered double hydroxides (LDHs) are often used as precursors for mixed-oxide catalysts and the deposition of a LDH layer on supporting materials would be advantageous because of better utilization of active components. Thepurpos eof thepre sent study was to investigateth eforma tion of LDHs on Al2O3/Al supports prepared by the anodic oxidation of aluminum foil in dilute aqueous solutions of Co, Mn, and/or Ni nitrates. The LDH deposition was carried out under hydrothermal conditions at 80-180ºC for periods ranging from 8 h to 7 days. In the initial stages of the reaction, a surface alumina hydration was observed. The LDH phase was detected after long-term deposition (3-7 days) at 120-160ºC and only a small amount of Mn was incorporated in the LDHs deposited. In solutions containing only Co and Mn cations, scanning electron microscopy (SEM) images show a gradual growth of platy crystals resulting in the formation of discrete bulky aggregates with sizes up to several tens of micrometers. The adhesion of aggregates to the support probably decreased with increasing size and oversized aggregates fell away; none was found in SEM images of the samples obtained after prolonged reaction times. When Ni cations were present in the solution, they were incorporated preferentially into the LDH phase; an homogeneous layer was formed, with single platy crystals oriented perpendicular to the support. After calcination at 500ºC, the products formed on Al2O3/Al support exhibited a shift of reduction maxima to higher temperatures in comparison with mixed oxides obtained by thermal decomposition of coprecipitated LDHs.
The Formation Of Layered Double Hydroxides On Alumina Surface In Aqueous Solutions Containing Divalent Metal Cations
gsccm57403-kov.pdf-- 995KB
Keywords: Periodicals; Geology; Deposition; Hydrothermal Reaction; Layered Double Hydroxides; Supported Mixed Oxides